Equipping lecturers with student-centric and learner-focused methods in response to evolving learner needs in foreign language instruction - Alshraah, Shadi Majed; Aly, Enas Mohamed S.; Alqasem, Mohammad Fayyad (Research Journal in Advanced Humanities, 2023)
This research aimed to investigate the effectiveness of training for foreign language instructors in adopting student-centered and learner-centric approaches to address evolving learner needs in foreign language education. The study assessed how student-centered teaching models impact the performance of foreign language students. Employing a mixed-methods approach, data were gathered through questionnaires and interviews, involving a sample of 152 lecturers and teacher trainers selected purposively. Both qualitative and quantitative analyses were conducted. The findings underscored the significance of learner autonomy, technological integration, and educators' willingness to adapt in enhancing effective foreign language education. The study emphasized the pivotal role of professional training in shaping the pedagogical landscape of foreign language education. Beyond equipping educators with learner-centric and student-centered methodologies, this training program empowered them to navigate the changing demands of language learners. Notably, the results aligned with the constructivist framework, highlighting its substantial influence in promoting active learning, autonomy, and collaboration in foreign language education. This research contributes to the growing body of evidence illustrating the essential role of professional development in fostering learner-centric and student-centered foreign language education, ultimately elevating the quality of language instruction and responsiveness to student requirements.